2023
DOI: 10.1332/239868021x16371459419254
|View full text |Cite
|
Sign up to set email alerts
|

Myths about myths? A commentary on Thomas (2020) and the question of jury rape myth acceptance

Abstract: This commentary responds to claims that research by Cheryl Thomas ‘shows’ no problem with rape myths in English and Welsh juries. We critique the claim on the basis of ambiguous survey design, a false distinction between ‘real’ jurors and other research participants, the conflation of attitudes in relation to abstract versus applied rape myths, and misleading interpretation of the data. Ultimately, we call for a balanced appraisal of individual studies by contextualising them against the wider literature.<b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Such research findings have thereby drawn into question the ability of jurors to fairly and impartiality evaluate the evidence presented within rape trials, particularly in respect of IPR cases where attitudes surrounding a man's right to have sex with his partner or wife have historically been widely endorsed. Recent research did find that rape mythology was not widely endorsed among genuine trial jurors (Thomas 2020); however, this study has been widely criticized based on the methodology employed (see Daly et al 2022). Indeed, most rape trial judges now warn against the endorsement of rape myths within English courtrooms when delivering a direction to jurors (Ellison 2019).…”
Section: Trial Lawyers and Jurorsmentioning
confidence: 84%
“…Such research findings have thereby drawn into question the ability of jurors to fairly and impartiality evaluate the evidence presented within rape trials, particularly in respect of IPR cases where attitudes surrounding a man's right to have sex with his partner or wife have historically been widely endorsed. Recent research did find that rape mythology was not widely endorsed among genuine trial jurors (Thomas 2020); however, this study has been widely criticized based on the methodology employed (see Daly et al 2022). Indeed, most rape trial judges now warn against the endorsement of rape myths within English courtrooms when delivering a direction to jurors (Ellison 2019).…”
Section: Trial Lawyers and Jurorsmentioning
confidence: 84%
“…However, there is ongoing debate surrounding the role of misconceptions about rape and broader sexual offences in juror decision-making. Thomas (2020) reported that “real” jurors show no such biases, although a group of researchers came together to challenge this conclusion based on the validity of the research (Daly et al , 2023). Given the ongoing debate as well as the fact that current research does not include the crime of sex trafficking, there is still a need for additional research on the role of gender and juror attitudes in decision-making within sex trafficking cases.…”
Section: Impact Of Gender On Juror Decision-makingmentioning
confidence: 99%
“…Some valid questions are raised by Leverick and others regarding the research methodology used by Thomas, and as Thomas uses a very different form of questions it can be argued that this work cannot simplistically be used to invalidate the 'rape myth' research discussed by Leverick (Chalmers et al, 2021;Daly et al, 2022). Nevertheless, her work is useful, at the very least, because it raises some doubts about the certainty of the idea that jurors are seriously prejudiced and that rape trial juries should be abolished.…”
Section: The Criticsmentioning
confidence: 99%